Brain–Machine Interfaces: Silk‐Enabled Conformal Multifunctional Bioelectronics for Investigation of Spatiotemporal Epileptiform Activities and Multimodal Neural Encoding/Decoding (Adv. Sci. 9/2019). Issue 9 (3rd May 2019) - Shi, Zhifeng; Zheng, Faming; Zhou, Zhitao; Li, Meng; Fan, Zhen; Ye, Huanpeng; Zhang, Shan; Xiao, Ting; Chen, Liang; Tao, Tiger H.; Sun, Yun‐Lu; Mao, Ying
Abstract : In article number1801617, Tiger H. Tao, Yun‐Lu Sun, Ying Mao, and co‐workers report clinical‐friendly silk‐supported/delivered soft bioelectronics with controllable loading/delivery of therapeutic molecules and parallel optical readouts of operating states for the investigation of spatio‐temporal epileptiform activities and neural encoding/decoding.